Oratory in Kazakh culture - Raev Дәулетбек; Seitkozha Елнур (Turkic Studies Journal, 2023)
The article is the first attempt in the local cultural studies to carry out a detailed study of the place and role of oratory in Kazakh culture. At the same time, the article considers the basics, cognitive episteme, methodological positions of the Kazakh eloquence as a continuum of general ethnocultural existence, anthropocentric, sociocentric, ethnocentric aspects of the art of eloquence, cultural and sophistic background of the nature and features of mobile thought in the context of eloquent verbal wisdom as a phenomenon-culture. At the same time, the study focuses on the cultural aspects of the cognitive-emotional impact of oratory on the perceiver. Along with this, the depth of presentation of thoughts to the audience in eloquent language and its axiological value are measured. Cultural and axiological meanings such as «beginning, presentation, content, warming up, fusion/ synthesis» within the framework of various rhetorical formulas are analyzed. Steps have been taken to reveal the cultural aspects of such concepts as «wrap/envelope,» «persuade,» and «confess» through the listener’s ability to convey a thought in rhetoric to other people through the poetic language. The problem of inseparability between eloquence and objective reality is analyzed through the prism of the Kazakh national-cultural moral ethos.